IMPROVEMENT OF METHODS FOR STIMULATING THE REPRODUCTIVE ACTIVITY OF COWS OF THE GOLSHTIN BREED - H. S. Urinov; Kuldashev O.U. (Bright Mind Publishing, 2025)
The article obtained results such as the effectiveness of vitamin and mineral feed additives in stimulating the reproductive function of Holstein cows and reducing their service life in conjunction with the prevention of gynecological diseases.
Keywords: Reproductive, stimulation, VILOFOSS, Renomix, premix, obstetric-gynecological, rectum, biotin, iron, copper, manganese, iodine, cobalt, selenium, calcium, magnesium, phosphorus, sodium, chlorine, sulfur.